PENGARUH KOMPETENSI KARYAWAN, KEPUASAN KERJA, DAN BEBAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT RIKAT ABADI MANUNGGAL JAKARTA - Alfina Putri Utami (2022)
This study is a quantitative research that aims to determine whether there is influence of employee competence, job satisfaction, and workload on Organizational Citizenship Behavior (OCB). This study uses 50 respondents from a population of employees who work at PT Rikat Abadi Manunggal with an exact number. The analysis technique used in this research is the path analysis method and data processing is done using SmartPLS 4.0. The results of the test show that (1) employee competency has a significant effect on Organizational Citizenship Behavior (OCB). (2) job satisfaction has a significant effect on Organizational Citizenship Behavior (OCB). (3) workload has a significant effect on Organizational Citizenship Behavior (OCB). (4) employee competence, job satisfaction, and workload have a significant effect on Organizational Citizenship Behavior (OCB).